2011
DOI: 10.1080/01457632.2010.483889
|View full text |Cite
|
Sign up to set email alerts
|

Heat Transfer Reduction due to a Ceiling-Mounted Barrier in an Enclosure with Natural Convection

Abstract: Effects of a ceiling-mounted barrier on natural convection heat transfer in

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
6
0

Year Published

2015
2015
2022
2022

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 17 publications
(6 citation statements)
references
References 39 publications
0
6
0
Order By: Relevance
“…Mahapatra et al [30] discovered the opposite combined convective stream in a partitioned box with two partitions attached in the bottom and top walls. Ilis et al [31] numerically explored the ceiling-mounted baffle on buoyant convection in a box. Khatamifar et al [32] inspected conjugate convective current in a box separated by a divider.…”
Section: Introductionmentioning
confidence: 99%
“…Mahapatra et al [30] discovered the opposite combined convective stream in a partitioned box with two partitions attached in the bottom and top walls. Ilis et al [31] numerically explored the ceiling-mounted baffle on buoyant convection in a box. Khatamifar et al [32] inspected conjugate convective current in a box separated by a divider.…”
Section: Introductionmentioning
confidence: 99%
“…Numerous studies have investigated the impact of fins in enclosures with a temperature gradient between the vertical walls along with the insulated top and bottom surfaces. Examples include: a single fin on the hot wall [15][16][17][18], a single fin on the insulated top wall [19], a single fin attached to either vertical (hot) or bottom (insulated) wall [20]. In contrast to these studies with laterally heated cavities, however, the research on augmentation or suppression of heat transfer in RB convection through fins is relatively limited.…”
Section: Introductionmentioning
confidence: 99%
“…It also revealed that the recirculation flow structure within the container significantly relies on the position and length of extended partitions. Ilis et al (2011) have discussed free convection in baffled square enclosures. In their work, the insulated baffle is located on the adiabatic top wall.…”
Section: Introductionmentioning
confidence: 99%